Demonstrating the impact of bidirectional coupling on the performance of an ocean-met model. (October 2017) - Rasheed, Adil; Süld, Jakob Kristoffer; Tabib, Mandar; Kvamsdal, Trond; Kristiansen, Jørn
Abstract: The mass, momentum and energy fluxes between the atmosphere and ocean surface depend on the state of the ocean surface. The fluxes in turn can significantly alter the nature of the marine boundary layer and the state of the ocean surface. These interactions can be modelled deterministically using a multiphase modelling approach or using a semi-stochastic approach. While the multiphase approach can give better insights (e.g. wave generation), it is computationally too expensive and not suited for modelling ocean waves which are inherently random in nature. It is for this reason that in a forecasting context, semi-stochastic approach is still the workhorse. Furthermore, even in a semi-stochastic approach ocean and atmospheric models can be coupled in either unidirectional way (ocean affecting the atmosphere) or bidirectional way (both ocean and atmosphere affecting each other). Current work compares the performance of these two coupling approaches and validates them using significant wave heights and 10m wind magnitude.